2017
DOI: 10.3390/s17010087
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Microfabricated Chip with Double Functions as an Ion Source and Air Pump Based on LIGA Technology

Abstract: The injection and ionization of volatile organic compounds (VOA) by an integrated chip is experimentally analyzed in this paper. The integrated chip consists of a needle-to-cylinder electrode mounting on the Polymethyl Methacrylate (PMMA) substrate. The needle-to-cylinder electrode is designed and fabricated by Lithographie, Galvanoformung and Abformung (LIGA) technology. In this paper, the needle is connected to a negative power supply of −5 kV and used as the cathode; the cylinder electrodes are composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…This demonstrated that the gas jet does not have an obvious effect on the discharge current. In contrast to Figure 6b of [23], it shows different characteristics. In Figure 6b, there are corona and glow discharges, apparently, when there is no gas flow.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…This demonstrated that the gas jet does not have an obvious effect on the discharge current. In contrast to Figure 6b of [23], it shows different characteristics. In Figure 6b, there are corona and glow discharges, apparently, when there is no gas flow.…”
Section: Resultsmentioning
confidence: 75%
“…The microchip works at ambient pressure and room temperature both with and without a N 2 supply. First, the discharge starts when N 2 is not supplied, which has been described in detail [23]. There were corona and glow discharges with the discharge voltage increasing from −3050 V to −3563 V.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations